Bridging the Divide between Science and Poetry: The Comparatist Legacy of Alexander von Humboldt. - Guest, Bertrand; Weber, Anne-Gaëlle (HiN - Alexander von Humboldt im Netz. Internationale Zeitschrift für Humboldt-Studien, 2025)
Which place can and should Alexander von Humboldt’s work occupy in literary studies and, more specifically, in comparative literature? Contemporary critical reading of his work has largely consisted of making it a possible and hitherto unknown source of new scientific disciplines. Humboldt has often been seen as the almost anachronistic author of a work that reconciled literary writing with scholarly requirements, at the very time when literature and science were being separated, and scientific disciplines were being specialised. Yet it appears that Humboldt, perfectly aware of the ongoing separation of the two fields, not only made the presuppositions explicit, but also proposed new ways of articulating literary and scholarly discourse. Better still, he experimented with several possible uses, between the literary and the scholarly, which redefine the boundaries and aims of both practices.